2021
DOI: 10.3855/jidc.13384
|View full text |Cite
|
Sign up to set email alerts
|

Facing COVID-19 pandemic: development of custom-made face mask with rapid prototyping system

Abstract: Background: COVID-19 is a global pandemic. The virus spreads through respiratory droplets and close contact. Therefore, the availability of personal protective equipment (PPE) for healthcare professionals is essential. 3D printing technology could represent a valid option to ameliorate PPE shortages. Methodology: Custom-made face mask were designed on the basis of facial scan and then 3D-printed. The whole protocol is executed with freeware software and only required a 3D printer. Six healthcare workers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Parameters that were taken into account during face mask analyses included qualitative fit testing, 24 quantitative fit testing, 19,22,43 filtration efficiency, 13,21 and overall comfort or discomfort (Table 3). 18,19,43 It is worth emphasizing that the use of 3D face scanning techniques allows for producing a mask with the highest degree of adhesion, and thus, tightness. 5,11,18 In order to increase the comfort wearing of a face mask obtained using AM techniques, the use of soft rim, most often made of silicone, has become common.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Parameters that were taken into account during face mask analyses included qualitative fit testing, 24 quantitative fit testing, 19,22,43 filtration efficiency, 13,21 and overall comfort or discomfort (Table 3). 18,19,43 It is worth emphasizing that the use of 3D face scanning techniques allows for producing a mask with the highest degree of adhesion, and thus, tightness. 5,11,18 In order to increase the comfort wearing of a face mask obtained using AM techniques, the use of soft rim, most often made of silicone, has become common.…”
Section: Discussionmentioning
confidence: 99%
“…18,19,43 It is worth emphasizing that the use of 3D face scanning techniques allows for producing a mask with the highest degree of adhesion, and thus, tightness. 5,11,18 In order to increase the comfort wearing of a face mask obtained using AM techniques, the use of soft rim, most often made of silicone, has become common. 5,22,34 Designs of a modified full-face diving mask with AM-made additives and an additional filter were also described.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3-D printing of two kinds (torturous or bifurcating) structures were analysed Reduce micron-sized particles from air at flow rates of 5 to 100 LPM at [ 56 ] Spider-net-like 2-D nanofiber (~ 30 nm) net structures were electrospun using 0.1 wt% LiCl in 4 wt% PAN/DMF High reduction (99.996%) of 0.3 µm PM were obtained at low thickness membrane of 0.4 µm with specific areal weightage of 0.68 g/m 2 [ 57 ] 3-D-printed 6 masks covers and maximized usage of one N95 fabric which can be used by single person to 6 persons. Performed user trials revealed good fit Rapid prototyping took ~ 33 min for 3-D design and printing took ~ 10 h [ 58 ] Rechargeable mask Triboelectric charge generation enhanced the filtration efficiency of disposable surgical mask and provided reusability Filtration efficiency doubled and stayed > 95% even after 10 times reuse by 80 °C disinfection [ 59 ] Various photobiocidal agents that can be regain biocide activity under sunlight after use in dark conditions Benzophenone tetracarboxylic dianhydride (BD) and chlorogenic acid (CA) exhibited highest reactive oxygen species generation [ 60 ] Comfort management Survey with 40 participants found comfort decreased with increasing pressure drop during exhalation. Different types of masks were tested Tight-fitting masks with small fans performed better than masks without fans [ 61 ] Reusable masks tested for air and water vapour permeability, thermal conductivity, and a wear trial Masks with thin fabric had good breathability.…”
Section: New Trends In Materials and Designs For Face Maskmentioning
confidence: 99%